Characterization of gas-liquid flows in rectangular bubble columns using conductivity probes - Buwa, Vivek V.; Ranade, Vivek V. (Chemical Engineering Communications, 2005)
Unsteady gas-liquid flows in bubble columns are comprised of various flow processes occurring with varying length and time scales and govern mixing and transport processes. In the present work, we have characterized dynamic and time-averaged properties of gas-liquid flows in rectangular bubble columns using conductivity probes. The development of a single-tip conductivity probe, data processing methodology, and photographic validation procedure is discussed in detail. The effect of superficial gas velocity and aerated liquid height-to-width ( H/W) ratio on voidage fluctuations and time-averaged gas holdup was investigated. The experimental data presented here can help in understanding the dynamics of various flow processes and validating computational fluid dynamics based models.
Keywords: Bubble column; gas holdup; gas-liquid flows; voidage fluctuations

Eulerian-lagrangian simulations of unsteady gas-liquid flows in bubble columns - Buwa, Vivek V.; Deo, Dhanannjay S.; Ranade, Vivek V. (International Journal of Multiphase Flow, 2006)
We studied the dynamics of gas-liquid flows in a rectangular bubble column using Eulerian-Lagrangian simulations. Three-dimensional, unsteady simulations were performed to simulate the dynamic characteristics of the oscillating bubble plume. The effect of superficial gas velocity and aerated liquid height-to-column width (HI K) ratio on the dynamic and time-averaged flow properties was studied and the simulated results were validated using wall pressure and voidage fluctuation measurements. The effect of lift force and numerical diffusion on the dynamic and time-averaged properties is discussed in detail. Further, the results obtained using the Eulerian-Lagrangian simulations were compared with the Eulerian-Eulerian simulations. The bubble scale information, which is otherwise lost in the Eulerian-Eulerian simulations, was validated using the voidage fluctuation measurements. Such experimentally validated Eulerian-Lagrangian models will be useful for the simulation of mass transfer and reactions in bubble columns. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Bubble column; CFD; Dynamics; Eulerian-Eulerian simulations; Eulerian-Lagrangian simulations; gas-liquid flow